2005
DOI: 10.4141/s04-077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical disturbance impacts on soil properties and lodgepole pine growth in British Columbia’s central interior

Abstract: M. 2005. Mechanical disturbance impacts on soil properties and lodgepole pine growth in British Columbia's central interior. Can. J. Soil Sci. 85: 681-691. Forest landings are areas located adjacent to haul roads where harvested trees that were skidded from the cutblock are processed and loaded onto trucks. Soils on landings are often excessively compacted by heavy timber harvesting machinery and may take many years to recover from such disturbance. This study examined soil properties and tree growth on unreha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
3
11
0
1
Order By: Relevance
“…In this study, with increasing traffic intensity from low to high, the percent of soil porosity decreased on all skidding trails; therefore, the lowest porosity is related to high traffic classes. These findings are in agreement with the results of McNabb et al (2001), Rab (2004) and Blouin et al (2005). The change in soil water content is one of the negative impacts of soil compaction because it decreases the soil volume, which eventually leads to a decrease in total soil porosity (Kachamba 2007).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, with increasing traffic intensity from low to high, the percent of soil porosity decreased on all skidding trails; therefore, the lowest porosity is related to high traffic classes. These findings are in agreement with the results of McNabb et al (2001), Rab (2004) and Blouin et al (2005). The change in soil water content is one of the negative impacts of soil compaction because it decreases the soil volume, which eventually leads to a decrease in total soil porosity (Kachamba 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Analogous to findings in other studies (Rab 1996, Blouin et al 2005, MP values decreased significantly with increasing traffic intensity and, to a minor extent, with an increasing slope of the skid trails. During timber harvesting operations, soil particles are rearranged and the continuity of pore spaces of both micro-and macro-pores may collapse.…”
Section: Macroporositysupporting
confidence: 87%
“…Nonetheless, a 20-year recovery period was insufficient for TP to approach values observed in undisturbed areas, particularly on primary skid trails, where TP were still about 15% lower. Blouin et al (2005) similarly observed that the lowest total porosity remained on landings and primary trails soils after a 23-year recovery period.…”
Section: Total Porositymentioning
confidence: 65%
“…stagnant water pools, and initiate gulley formation and washouts along slopes (Carter et al 2000(Carter et al , 2007Blouin et al 2005;Foltz 2006). Activities intended to curb negative soil disturbance effects refer to (1) seasonally imposed rules and regulations for on-and off-road vehicular transport, (2) adherence to agreed upon best management practices and related certification requirements with respect to minmizing soil disturbances, and (3) follow up in terms of quality control by way of soil disturbance monitoring and best management practice effectiveness evaluations, recommendations, and guidelines (Duckert et al 2008;Miller et al 2010).…”
mentioning
confidence: 99%